2021
DOI: 10.1007/s00467-021-05084-x
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of acute kidney injury in pediatric COVID-19 patients in the intensive care unit

Abstract: Background and objectives COVID-19 is responsible for the 2019 novel coronavirus disease pandemic. Despite the vast research about the adult population, there has been little data collected on acute kidney injury (AKI) epidemiology, associated risk factors, treatments, and mortality in pediatric COVID-19 patients admitted to the ICU. AKI is a severe complication of COVID-19 among children and adolescents. Methods A comprehensive literature search was conducted in PubMed/MEDLINE and Cochrane Center Trials to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 39 publications
1
22
0
3
Order By: Relevance
“…We observed that AKI incidence in children with acute COVID-19 is almost similar to critically sick children admitted for other illnesses [ 1 ]. A similar incidence of AKI is also reported in adults with COVID-19 [ 3 , 4 ]. Considering a significant proportion of children with SARS-CoV-2 infection developing AKI, clinicians should be watchful and take pre-emptive measures for prevention.…”
supporting
confidence: 76%
“…We observed that AKI incidence in children with acute COVID-19 is almost similar to critically sick children admitted for other illnesses [ 1 ]. A similar incidence of AKI is also reported in adults with COVID-19 [ 3 , 4 ]. Considering a significant proportion of children with SARS-CoV-2 infection developing AKI, clinicians should be watchful and take pre-emptive measures for prevention.…”
supporting
confidence: 76%
“…AKI is one of the most common complications of COVID-19 and is estimated to occur in up to 30% of paediatric patients. 2 The aetiology is probably multifactorial but includes cytokine storm, macrophage and complement activation; endothelial dysfunction; and direct viral infection of podocytes and tubular cells. There are very few reports, however, of children with COVID-19 developing AKI secondary to rhabdomyolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing severity of the myalgia however triggered further investigation and the identification of a significant AKI. AKI is one of the most common complications of COVID‐19 and is estimated to occur in up to 30% of paediatric patients 2 . The aetiology is probably multifactorial but includes cytokine storm, macrophage and complement activation; endothelial dysfunction; and direct viral infection of podocytes and tubular cells.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the reviews excluded studies with < 10 patients, published in languages other than English, and on specialized populations i.e., children, pregnant women, and patients with cancer and CKD. One review was conducted on the pediatrics population (44), while five studies included KTRs in data synthesis (21,31,34,36,37). All the reviews did not include animal studies, and most of the reviews excluded case reports, except five studies (1,11,13,21,45).…”
Section: Characteristics Of Included Reviewsmentioning
confidence: 99%